An object relational psychoanalysis of selected Tennessee Williams play texts - Tosio, Paul (Rhodes University, Faculty of Humanities, Department of Drama, 2003)
Tennessee Williams is a playwright of great psychological depth. This thesis probes some of the complexities of his work through the use of Object Relational Psychoanalysis, specifically employing the theories of Melanie Klein, W.R.D. Fairbairn and Donald Winnicott. The Glass Menagerie, A Streetcar Named Desire, Cat On A Hot Tin Roof and The Night of The Iguana are analysed from this theoretical stance. All of these plays display great perceptiveness into the human condition, accurately portraying many psychological relational themes. Certain Object Relational themes become very apparent in these analyses. These themes include, Dependency (especially in The Glass Menagerie), Reparation (particularly in A Streetcar Named Desire), Falsehood (notably in Cat on a Hot Tin Roof), Idealisation (evident in The Night of The Iguana), Honest Empathetic Relations (apparent in Cat on a Hot Tin Roof and The Night of The Iguana) as well as Guilt, Object Loss, Sexual Guilt, and Obligation (recurring throughout these plays). It is advanced that Williams' plays posses an honest and insightful understanding of human relations and, as such, are of contemporary value. This Thesis is not only an academic study, but also has practical applications for dramatists. With an increased understanding of the intrinsic tensions and motivations within such plays, offered by such psychoanalytic strategy, performance and staging of such work may be enhanced valuably.
Keywords: Williams, Tennessee, 1911-1983; Williams, Tennessee, 1911-1983 -- Knowledge -- Psychology; Object relations (Psychoanalysis); Psychoanalysis Drama -- Psychological aspects